Isolation, Characterization, and Identification of Bacterial Population from Textile and Tannery Effluents of Bangladesh (Bangladesh Journal of Microbiology, 2016)
Ten effluent samples from two different sites located at Hazaribagh tannery belt and Dhaka EPZ, Savar were collected. This study aimed to compare the bacterial composition isolated from tannery and textile effluents and to investigate the occurrence of metal toxicity tolerant and dye degrading bacteria and to select the potential strains for the use in bioremediation. The average bacterial count of HT and DETDE varied in between 3.35×106 and 5.45×106 cfu/mL and 4.8×106 and 7.75×106cfu/mL, respectively. A total of 12 bacterial isolates were characterized as strains of Bacillus, Staphylococcus, and Pseudomonas. A few, however, were re-cultured on other recommended media for verification of diagnostic characteristics. Maximum numbers of bacterial species were isolated from textile effluent. The results showed that a Gram-positive bacillus with a yellow pigment was considered as a major group of the population. Among them three isolates were identified based on alignments of partial sequence of 16S rRNA gene. These are also being used in different wastewater and metal treatment plants all over the world.Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 84-88